ISO 9001 : 2000 training (Makati City, Philippines : ECCInternational, 2001)
Contents: trainings, ISO 9001:2000, document control; printable documents, checklists, procuders and forms, ISO 9000 standards, series; interactive exam
System requirements: Pentium II Processor 300Mhz, 64MB RAM, 8x CD-ROM, Windows 95/98/ME/2000, mouse, sound card and speakers, (recommended: Pentium III Processor 600Mhz, 32x CD-ROM)
Keywords: Quality assurance; ISO 9001 Standard; ISO 9000 Series Standards